Legal Review of The Criminal Act of Child Molestery - Falihah Qomala; Bastianto Nugroho; Sri Anggraini K. Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The aim of this research is to determine the application of material criminal law to cases of ongoing child abuse in decision Number 1271/Pid.Sus/2020/PT Sby. This research method is normative research, with a conceptual approach, namely legal research that looks for principles, doctrines and sources of law in a juridical philosophical sense. Results: Efforts to protect against identity reporting through mass media and to avoid labeling, providing safety guarantees for victim witnesses and expert witnesses, both physical, mental and social and providing accessibility to obtain information regarding case developments as well as support from the government or related institutions as well as from community members and those closest to them, case assistance from case examination to trial from the Women and Child Protection (PPA) unit and the social department.